The social dimension of CSR: Towards regulation - EL HADANI , Kawtar; BELAMIN, Samir (Revue Internationale du Chercheur, 2025)
Abstract Despite the use of the term "responsibility" within the very concept of Corporate Social Responsibility (CSR), it is essential to emphasize that this approach remains primarily a voluntary initiative adopted by companies, especially employers. It is not accompanied by any form of sanctions and thus does not directly constrain them in terms of their responsibility. However, the legal and judicial reality unfolds with a wealth of nuances. Indeed, in the social realm, CSR undeniably generates legal obligations that can potentially have significant repercussions. As a result, this article aims to explore the complex interplay between the inherent voluntary nature of CSR and the legal imperatives it can establish within the societal context.